Structural Stability Analysis of Models of Dopamine Synthesis and D1 Receptor Trafficking in RPT Cells using CRNT. - Villar, J.J.
Dopamine plays an important role in different physiological and metabolic functions, including the control of sodium excretion in the kidney. Studies have shown that there is a positive correlation between a defect in dopamine synthesis and/or dopamine receptor function, and a defect in renal sodium excretion ? which may lead to the development of essential hypertension. Specific receptors for dopamine, such as the D1 receptor, have been identified in the various regions within the kidney. It is observed that errors regarding dopamine receptor-G protein coupling and changes in the signaling components may be responsible for the failure of dopamine to increase sodium excretion in hypertensive subjects. In this paper, two symbolic kinetic models of dopamine synthesis and one of dopamine D1 receptor trafficking are presented. The three models are chemical reaction networks constructed and analyzed using Chemical Reaction Network Theory (CRNT), a framework that provides different insights on the static properties of a chemical reaction network regarding the existence of steady states, their multiplicity, and structural stability. It is found that all three networks do not support multiple steady states.
Keywords: Science -- Periodicals; Chemical reaction network theory; Concentration robustness; Renal dopaminergic system; DI receptor trafficking; Structural stability analysis